Integrated waste processing in pangandaran beach tourism area. Issue 1 (1st November 2022) - Kastolani, W; Darsiharjo,; Setiawan, I; Supriatna, U
Abstract: Pangandaran Beach is one of the iconic tourist destinations in the province of West Java. This beach tourism area is a favorite of local tourists with a number of 3.9 million tourists at the end of 2018. The large number of tourist visits to Pangandaran Beach in addition to being economically profitable, also has a negative impact in the form of waste generation. Tourism activities produce organic waste in the form of hotel and restaurant food scraps and then inorganic waste such as plastic food wrappers, plastic bottles and others. Based on these problems in the research plan for three years, divided into three main focuses, namely in the first year is how integrated waste management for Pangandaran Beach tourism area. The focus of the second year research is the processing of waste from the food and beverage industry in Pangandaran Regency and in the third year is processing organic waste for freshwater fish feed. The research method used in the first year research is a descriptive method that aims to describe how waste processing has been done so far, community participation and how integrated waste management is in the Pangandaran Beach tourism area. Based on the results of the study, it was found that the processing of waste in the tourist area is still by collecting-transporting-dumping, the final disposal site (TPA) uses an open dumping system that is the garbage is disposed of without any treatment. Community participation in waste processing is in the medium category (score 56.5%) and integrated waste processing is still in the early stages of development.